Last evening, after reading a couple of questions about nested radicals, I started to wonder about problems involving what I will term "alternating nested radicals;" below is an example, which I found here.

Prove the convergence of, and evaluate, $\sqrt{7 -\sqrt{7 + \sqrt{7...}}}$

It turns out that this nested radical converges to $2$, and this is not especially hard to argue on an ad-hoc basis. However, I became interested in the general solution of the problem of evaluating $\sqrt{q -\sqrt{q + \sqrt{q...}}} \text{ }\text{ }$ for an arbitrary positive real $q$. Despite some searching, I was not able to find a paper which stated a theorem on this, so I resorted to working it out for myself.

I have developed an argument which I believe gives the correct result for all $q > 1.$ I have checked its predictions against several alternating nested radicals, and they agree with computation.

Theorem: $\sqrt{q -\sqrt{q + \sqrt{q...}}} = \frac{\sqrt{1 + 4(q-1)}-1}{2}$

Argument: We make two significant assumptions:

  • that $\sqrt{q -\sqrt{q + \sqrt{q...}}} \text{ }\text{ }$ converges; and,
  • inspired by the fact that $\sqrt{q +\sqrt{q + \sqrt{q...}}} \text{ }\text{ } = x$ satisfies $x^2 - x - q = 0$, we assume that $\sqrt{q -\sqrt{q + \sqrt{q...}}} \text{ }\text{ } = x$ satisfies $x^2 + x - a$ for some $a$.

By the self-similarity of the alternating nested radical, we find

\begin{align} \sqrt{q - \sqrt{q + x}} &= x \\ q - \sqrt{q + x} &= x^2 \\ &= a-x \\ \therefore q + x - \sqrt{q + x} &= a \end{align}

Solving this as a quadratic in $\sqrt{q+x}$ yields $$\sqrt{q+x} = \frac{\sqrt{1 + 4a} + 1}{2}.$$ Again using our second assumption, we have $$x = \frac{\sqrt{1 + 4a} - 1}{2}.$$ But now

$$ \sqrt{q+x} - x = \frac{\sqrt{1 + 4a} + 1}{2} - \frac{\sqrt{1 + 4a} - 1}{2} = 1$$

and so we get

$$ q+x = (1+x)^2$$

and thus

$$ x^2 + x - (q-1) = 0.$$

Solving this quadratic for $x$ then gives the theorem.

I am pretty sure that my second assumption above would be impossible to defend; so, basically, I have the following questions:

  • How can we rigorously prove that the alternating nested radical converges?
  • How can we show, for a general $q$, that it converges to the value given in the theorem?

And one other thing: any general references to ubiquitous convergence theorems or techniques would be greatly appreciated!


Consider the function $f(x) = \sqrt{q - \sqrt{q+x}}$. If we don't want to allow square roots of negative numbers, we need $x \ge -q$ and $q \ge \sqrt{q+x}$, so $x \le q^2 - q$. On the interval $[-q, q^2 - q]$, $f$ is easily seen to be decreasing, with $$f'(x) = -\frac{1}{4 \sqrt{q - \sqrt{q+x}} \sqrt{q+x}}$$ Note also that $f(-q) = \sqrt{q}$ and $f(q^2-q) = 0$. $f$ has a unique fixed point on the interval as long as $q^2 - q \ge 0$, i.e. $q \ge 1$. This fixed point turns out to be $$p = \dfrac{-1+\sqrt{4q-3}}{2}$$ Now $f'(p) = -1$ for $q = 5/4$. When $q < 5/4$, $f'(p) < -1$ and the fixed point is unstable. When $q > 5/4$, $f'(p) > -1$ and the fixed point is stable. When that is true, there is some interval around $p$ such that the recursion $x_{n+1} = f(x_n)$, started at any $x_0$ in the interval, tends to the limit $p$. That gives some justification to identifying $\sqrt{q - \sqrt{q + \sqrt{q - \sqrt{\ldots}}}}$ as $p$.


Let $R_0 =S_0 =\sqrt{q}$ and define the recurrences $$A_{n+1}=\sqrt{q + S_n}$$ and $$S_{n+1}=\sqrt{q - A_n}.$$ Then your nested radical is simply $\lim_{n \to \infty}S_n$. If $q>\sqrt{q + \sqrt{q}}$, then you can show by induction that for all $n>0$, $$0<S_n \leq \sqrt{q} \leq A_n \leq \sqrt{q + \sqrt{q}}. $$ Now $\{A_n\}$ clearly converges (by calculus), and this can be used to show $\{S_n\}$ is Cauchy.

Assuming convergence, let $R=\lim_{n \to \infty} S_n$. To evaluate the limit, notice $$ R = \sqrt{q - \sqrt{q+R}}, $$ the solutions of which are among the solutions of $(R^2-q)^2=q+R$. Solving polynomial for $R$, and eliminating the negative solutions, we have $$ R= \frac{1 + \sqrt{4q+1}}{2} $$ or $$ R= \frac{-1 + \sqrt{4q-3}}{2}. $$ So the limit must be one of these solutions, if it exists.

It sounds like you have some good reason for believing the correct value is $\frac{1}{2}(-1 + \sqrt{4q-3})$, so I'll stop here.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.